Exosomal CD73 from serum of patients with melanoma suppresses lymphocyte functions and is associated with therapy resistance to anti-PD-1 agents - Mariaelena Capone; Gabriele Madonna; Ester Simeone; Paolo A Ascierto; Antonio Sorrentino; Roberta Turiello; Elva Morretta; Maria Chiara Monti; Rosa Azzaro; Silvana Morello; Pasquale Del Gaudio (Journal for ImmunoTherapy of Cancer)
Background CD73 is an ectonucleotidase producing the immunosuppressor mediator adenosine. Elevated levels of circulating CD73 in patients with cancer have been associated with disease progression and poor response to immunotherapy. Immunosuppressive pathways associated with exosomes can affect T-cell function and the therapeutic efficacy of anti-programmed cell-death protein 1 (anti-PD-1) therapy. Here, we conducted a retrospective pilot study to evaluate levels of exosomal CD73 before and early during treatment with anti-PD-1 agents in patients with melanoma and its potential contribution to affect T-cell functions and to influence the clinical outcomes of anti-PD-1 monotherapy.Methods Exosomes were isolated by mini size exclusion chromatography from serum of patients with melanoma (n=41) receiving nivolumab or pembrolizumab monotherapy. Expression of CD73 and programmed death-ligand 1 (PD-L1) were evaluated on exosomes enriched for CD63 by on-bead flow cytometry. The CD73 AMPase activity was evaluated by mass spectrometry, also in the presence of selective inhibitors of CD73. Interferon (IFN)-γ production and granzyme B expression were measured in CD3/28 activated T cells incubated with exosomes in presence of the CD73 substrate AMP. Levels of CD73 and PD-L1 on exosomes were correlated with therapy response. Exosomes isolated from healthy subjects were used as control.Results Isolated exosomes carried CD73 on their surface, which is enzymatically active in producing adenosine. Incubation of exosomes with CD3/28 activated T cells in the presence of AMP resulted in a significant reduction of IFN-γ release, which was reversed by the CD73 inhibitor APCP or by the selective A2A adenosine receptor antagonist ZM241385. Expression levels of exosomal CD73 from serum of patients with melanoma were not significantly different from those in healthy subjects. Early on-treatment, expression levels of both CD73 and PD-L1 on exosomes isolated from patients receiving pembrolizumab or nivolumab monotherapy were significantly increased compared with baseline. Early during therapy exosomal PD-L1 increased in responders, while exosomal CD73 resulted significantly increased in non-responders.Conclusions CD73 expressed on exosomes from serum of patients with melanoma produces adenosine and contributes to suppress T-cell functions. Early on-treatment, elevated expression levels of exosomal CD73 might affect the response to anti-PD-1 agents in patients with melanoma who failed to respond to therapy.